Planejamento da distribuição de lotes de vagões vazios a partir de pátios de triagem para atendimento à demanda de carregamento das minas - Pereira, Hendrigo Venes (2019)
Brazilian railroads are responsible for 20.7% of the cargo transportation in the country, such as: iron ore, grains, steel products, cement, lime, fertilizers, petroleum products, lime, coal, clinker, containers, among others (CNT, 2018). Iron ore (FeO) represents 77.45% of the total percentage of Brazilian cargo transportation (ANTT, 2019). Among the companies in Brazilian rail market is Vale S / A, the company is responsible for the management of the Vitória Minas Railroad (EFVM). EFVM carries out the iron ore transport of the 13 Vale S / A mines in the State from Minas Gerais to the Port of Tubarão in Espírito Santo. However, the wagons return empty to load in the mines. This paper aims to propose a mathematical model of Mixed Integer Linear Programming for distribution of wagons from sorting yards to meet the demand for empty wagons in the mines. Using the CPLEX 12.8 solver to execute the model, a methodology was developed to minimize the dismemberment of lots of wagons in the sorting and origin yards, in addition to minimizing the trains' travel time. Using EFVM data, it was possible to compare the distributions and it was found that CPLEX finds optimal solutions in very low execution times, distributing batches of empty wagons with less dismemberment than manual distribution done by EFVM team.